ChemInform Abstract: Sulfinyl‐Mediated Stereoselective Overman Rearrangements and Diels—Alder Cycloadditions. Issue 41 (September 2016) - Colomer, Ignacio; Gheewala, Chirag; Simal, Carmen; Velado, Marina; Fernandez de la Pradilla, Roberto; Viso, Alma
Abstract: Trichloroacetamidates are used as substrates in the title rearrangement to produce the desired allylic amine synthons in a highly stereoselective manner as is demonstrated for a few examples.